EXPLANATION
Given that the triangles are congruent, it means that the sides are also congruent.
Therefore, we can assevere that the sum of sides from one triangle is equal to the sum of sides from the other.
(3x+4) + (2x+4) + (2x+1) = (3x-3) + (4x-3) + (x+8)
Removing the parentheses:
3x + 4 + 2x + 4 + 2x + 1 = 3x - 3 + 4x - 3 + x + 8
Adding like terms:
7x + 9 = 8x + 2
Switching sides:
8x + 2 = 7x + 9
Subtracting -7x to both sides:
8x - 7x = 9 - 2
Subtracting like terms:
x = 7
The value of x is x=7